2010
DOI: 10.1159/000319004
|View full text |Cite
|
Sign up to set email alerts
|

Serum Biochemical Markers for Brain Damage in Children with Emphasis on Mild Head Injury

Abstract: Despite the high incidence of mild pediatric head injuries, only within the past few years has there been increased interest and research in this area. This interest began when the findings from research done in adult patients showed that the effects of mild closed head injuries could interfere significantly with higher cognitive functioning, which impacted daily activities and employment. Traumatic brain injury (TBI) often involves a combination of mechanical trauma and local hypoxemia, on which serum biomark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 77 publications
0
6
0
Order By: Relevance
“…Based on these prior studies and the fact that neurologic injury commonly occurs in infants and children with CHD, we hypothesized that SBDPs would be readily detectable in the serum of neonates with CHD in the perioperative period. Because accessing CSF is impractical following heart surgery, the ability to detect SBDPs in circulating blood carries importance because candidate biomarkers should be able to cross the blood-brain barrier following injury to enable ease of measurability (21). Furthermore, because alpha II-spectrin is not found in RBCs, breakdown of the protein and generation of SBDPs are not confounded by hemolysis commonly encountered during heart surgery (3).…”
Section: Discussionmentioning
confidence: 99%
“…Based on these prior studies and the fact that neurologic injury commonly occurs in infants and children with CHD, we hypothesized that SBDPs would be readily detectable in the serum of neonates with CHD in the perioperative period. Because accessing CSF is impractical following heart surgery, the ability to detect SBDPs in circulating blood carries importance because candidate biomarkers should be able to cross the blood-brain barrier following injury to enable ease of measurability (21). Furthermore, because alpha II-spectrin is not found in RBCs, breakdown of the protein and generation of SBDPs are not confounded by hemolysis commonly encountered during heart surgery (3).…”
Section: Discussionmentioning
confidence: 99%
“…Because of the non-specificity of subjective postconcussive complaints, any lack of a residual biomarker objectively identifying the presence or absence of brain injury limits characterization of injured participants from a neuropsychological standpoint. The 25 reference studies were conducted prior to current objective biomarkers of injury such as those found with diffusion tenor imaging (DTI) and other neuroimaging techniques (Kou et al, 2010;Niogi & Mukherjee, 2010), eye tracking or ocular convergence as a reflection of brainstem integrity (Contreras, Ghajar, Bahar, & Suh, 2011;Heitger et al, 2009), blood biomarkers (Dash, Zhao, Hergenroeder, & Moore, 2010;Kovesdi et al, 2010;Menascu, Brezner, Tshechmer, & Rumeny, 2010), or postural stability (Sheedy, Harvey, Faux, Geffen, & Shores, 2009;Slobounov, Cao, Sebastianelli, Slobounov, & Newell, 2008)-to list the most promising current biomarkers. As previously discussed, the recent studies by Messe et al (2011) andHeitger et al (2009) unmistakably show the importance of using a biomarker when investigating the effects of mTBI.…”
Section: Data Transparency: the Meta-analysis Spread Sheetmentioning
confidence: 99%
“…TBI often involves a combination of mechanical trauma and local hypoxemia, on which serum biomarker concentrations may provide critical therapeutic data to evaluate the brain injury. Serum biomarker after TBI could be used as a source for the identification of the brain injury, the extent of the injury, and the time of its occurrence and even for identifying its most likely outcome [ 41 ].…”
Section: Discussionmentioning
confidence: 99%